Fusion magnet quench risk increase with irradiation damage - Jacob M. John; Mark R. Gilbert; Chris D. Hardie (Nuclear Fusion, 2025)
Superconducting material enables fusion reactor magnet concepts to operate with current densities that would melt materials with non-zero resistance. The application of superconducting material is considered essential for net-positive power machines. Catastrophic damage can occur when superconductivity is lost and the current generates heat. This scenario is called a quench. Stabilizer material carries the magnet current (typically copper) during a quench and is the focus of this work. Irradiation-induced defects store energy in the Cu crystalline lattice. The presence of defects reduces thermal conductivity (thermally insulating the superconductor), electrical conductivity (increasing temperature ramp rate during a quench), and specific heat capacity (increasing thermodynamic instability). The release of stored energy in the magnet materials, in combination with the magnet material property changes, has the potential to cause extreme off-normal events in superconducting magnets that worsen with fluence. Stored energy can be released causing local heating and increasing the risk of a quench. For example, following irradiation at 4.6 K and a fluence of 0.45×10 ^18 n cm ^−2 , an energy release of 0.023 J g ^−1 was measured from Cu when increased in temperature from 10 K to 18 K, which would have been enough energy to create the same temperature increase spontaneously. Extrapolations of experimental data are used to estimate when spontaneous heating can occur due to the release of energy stored in irradiation-induced defects. Critical fluence values are estimated between 1.74×10 ^18 n cm ^−2 and 2.85×10 ^19 n cm ^−2 for neutron irradiation of Cu at a temperature of 20 K. In-situ cryogenic calorimetry experiments, operated at high-temperature-ramp rates on irradiated magnet materials, could offer certainty for fusion magnet system designers. Periodic annealing of defects through controlled temperature cycling will be essential in fusion power plants to manage the increasing risk of quench as the superconducting magnets accumulate dose. The ideal frequency and dynamics of these maintenance temperature cycles will be established with further experimental examination.